2008
DOI: 10.1007/s10195-008-0015-5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue sparing surgery in knee reconstruction: unicompartmental (UKA), patellofemoral (PFA), UKA + PFA, bi-unicompartmental (Bi-UKA) arthroplasties

Abstract: Recently mini-invasive joint replacement has become one of the hottest topics in the orthopaedic world. However, these terms have been improperly misunderstood as a "key-hole" surgery where traditional components are implanted with shorter surgical approaches, with few benefits and several possible dangers. Small implants as unicompartmental knee prostheses, patellofemoral prostheses and bi-unicompartmental knee prostheses might represent real less invasive procedures: Tissue sparing surgery, the Italian way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…MIS techniques are believed to reduce blood loss in TJA procedures, included the so-called tissue sparing surgery [8185].…”
Section: Resultsmentioning
confidence: 99%
“…MIS techniques are believed to reduce blood loss in TJA procedures, included the so-called tissue sparing surgery [8185].…”
Section: Resultsmentioning
confidence: 99%
“…Following a standardized protocol [13], all of the ultrahigh-molecular-weight polyethylene tibial inserts were pre-soaked for 4 weeks prior to the wear tests to achieve a steady level of fluid sorption. One medial and one lateral pair of femoral and tibial components were mounted on each station to reproduce the mounting configuration of a Bi-UKR [2,11,17].…”
Section: Specimensmentioning
confidence: 99%
“…Although earlier PFJ prostheses were noted to have poor outcomes [ 7 ] more recent studies have shown substantially better results [ 8 10 ]. One of the commonest indications for PFJ revision surgery is osteoarthritic progression of the tibiofemoral compartments [ 7 , 11 ]. The improvement of PFJ replacement surgery is attributable to improved implant designs, better patient selection and improved surgical technique [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The limited available literature has been complicated by studies coalescing the results of combined medial and lateral UKRs, medial UKR plus PFJ replacement, lateral UKR plus PFJ replacement and monolithic (femoral monobloc) prostheses all being analysed together. Previous reports [ 11 , 13 , 15 , 16 ] of this concept of partial replacement surgery have suggested a significant difference in the survival between these different surgical procedures. We propose a separate modular bicompartmental classification of bi-unicompartmental (combined medial and lateral UKRs), medial segmental (medial UKR plus PFJ replacement) and lateral segmental (lateral UKR plus PFJ replacement) to accurately distinguish between these different surgical techniques and allow greater clarification in the literature when comparing results of studies.…”
Section: Introductionmentioning
confidence: 99%